Determinants of sexually transmitted infections among female sex workers in Ethiopia: a count regression model approach - Wariso, Feyiso Bati; Ayalew, Jemal; Barba, Ammar; Bedassa, Birra Bejiga; Ebo, Gemechu Gudeta; Tura, Jaleta Bulti; Rameto, Mohammed; Belihu, Wudinesh Belete; Asfaw, Derbachew; Amogne, Minilik Demissie; Negeri, Lemessa; Lulseged, Sileshi; et al. (Frontiers in Public Health, 2023)
Background Sexually transmitted infections (STIs) remain a major public health problem worldwide, with the burden of these infections being high among female sex workers (FSWs), who are often not aware of their infection status. This study aimed to determine the factors that are associated with the number of STIs among FSWs in Ethiopia. Methods A cross-sectional bio-behavioral study involving respondent-driven sampling (RDS) was conducted among 6,085 FSWs in 16 towns in Ethiopia. The hurdle Poisson regression model was fitted using STATA Version 16.2. The incident rate ratio and adjusted odds ratio with a 95% confidence interval were employed to show the strength and direction of the association. A p-value of ≤0.05 was used as a threshold for statistical significance. Results At least one STI was identified in 1,444 (23.64%) of the FSWs. Age group 35–49 years [IRR = 2.32; 95% CI (1.43, 3.74)], forced first sex [IRR = 1.32; 95% CI (1.01, 1.74)], condom breakage [IRR = 1.32; 95% CI (1.01, 1.74)], and a history of depression [IRR = 1.55; 95% CI (1.12, 2.18)] increase the number of STIs. FSWs aged 25–34 years [AOR = 2.99; % CI (2.54, 3.52)] and 35 = 59 years [AOR = 8.05; % CI (6.54, 9.91)], who were selling sex for 5–10 years [AOR = 1.30; 95% CI (1.1, 1.55)], and above 11 years [AOR = 1.21; 95% CI (1.03, 1.43)] were more likely to get STIs. Conclusion STIs are common in Ethiopia. The covariates age, educational status, monthly income, condom failure, age at the first sexual encounter, and long duration of sexual practice are significant predictors of STIs. Health interventions among FSWs need to include awareness generation about the prevention and control of STIs and address the determinants identified in this analysis.